DOUBLE FREE FUNCTIONING MUSCLE TRANSFERS FOR BRACHIAL PLEXUS INJURIES: A CASE REPORT - Heri Suroto; Teddy Heri Wardhana; Farindra Ridhalhi (Journal Orthopaedi and Traumatology Surabaya, 2019)
Free functional muscle transfer for brachial plexus injury is one of the alternatives to repair the upper extremity function, where usually one type of muscle is used, the gracillis. The method of using two donor muscles to restore the motor function is worth considering for a better improvement of the quality. A 36 years old man with a complete left brachial plexus injury from C5-T1 due to motorcycle accident. A double free functional muscle transfer was performed using the gracillis muscle and the adductor longus muscle with the arterial source from the thoraco-acromial artery with the phrenic and accessory nerves. The gracillis muscle is used to flex the fingers while the adductor is used for flexing the elbow. A one year post-operative evaluation showed the patient was already capable of flexing his elbow with the muscle score of 3 and also the fingers with the muscle score of 1. The double free functional muscle transfer procedure is effective in achieving the moving function of both the elbow and the hand.